2021
DOI: 10.1371/journal.pone.0247020
|View full text |Cite
|
Sign up to set email alerts
|

CYP4B1 is a prognostic biomarker and potential therapeutic target in lung adenocarcinoma

Abstract: CYP4B1 belongs to the mammalian CYP4 enzyme family and is predominantly expressed in the lungs of humans. It is responsible for the oxidative metabolism of a wide range of endogenous compounds and xenobiotics. In this study, using data from The Cancer Genome Atlas (TCGA) project and the Gene Expression Omnibus (GEO) database, a secondary analysis was performed to explore the expression profile of CYP4B1, as well as its prognostic value in patients with lung adenocarcinoma (LUAD). Based on the obtained results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…CYP4B1 is a member of the CYP4B subfamily, and the current researches on CYP4B1 gene mainly focus on its function analysis. Studies have shown that CYP4B1 plays an important role in the metabolic process of endogenous compounds and exogenous substances (drugs, environmental toxicants, pro-carcinogens), thereby affecting the occurrence and development of diseases [15]. It is well known that the drug metabolizing enzymes in the human body are also the metabolic enzymes of important carcinogens, which control and affect the metabolism of carcinogens, so they play a decisive role in tumor susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…CYP4B1 is a member of the CYP4B subfamily, and the current researches on CYP4B1 gene mainly focus on its function analysis. Studies have shown that CYP4B1 plays an important role in the metabolic process of endogenous compounds and exogenous substances (drugs, environmental toxicants, pro-carcinogens), thereby affecting the occurrence and development of diseases [15]. It is well known that the drug metabolizing enzymes in the human body are also the metabolic enzymes of important carcinogens, which control and affect the metabolism of carcinogens, so they play a decisive role in tumor susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…CYP4B1 is a member of the cytochrome P450 superfamily of monooxygenases that catalyze drug metabolism and synthesis of cholesterol, steroids, and other lipids [ 21 ]. Studies have uncovered the role of CYP4B1 in the oxidation of fatty acids, activation of procarcinogens and neovascularization, and the promising potential as a target in cancer treatment [ 22 , 23 ]. PLK1 is a Serine/Threonine protein kinase of the CDC5/Polo subfamily and a critical cell cycle regulator frequently overexpressed in cancers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of CYP4B1 gene expression is related to bladder urothelial carcinoma (51), and its low expression is related to the poor prognosis of LUAD patients. Therefore, it can be used as an independent prognostic marker and a potential therapeutic target for patients with LUAD (52).…”
Section: Discussionmentioning
confidence: 99%